PENGALAMAN PEREMPUAN UNTUK MENENTUKAN HAK-HAK REPRODUKSI PADA PERNIKAHAN DINI - ita yuliani (Politeknik Kesehatan Kemenkes Malang (State Health Polytechnic of Malang), 2020)
Many people do not know women's reproductive rights. Women are easier to make a list of obligations than their rights (Amirrudin, 2003). The experience of respondents to determine women's reproductive rights is subjective (felt, lived) both new (1 year) and long (24 years). Respondents experienced early marriages, namely marriage in adolescence (16-19 years). The study was in Gunungrejo Village, Singosari Sub-District, Malang Regency, with the time of August to Novembar 2018. The design of this study was qualitative descriptive. Technique of collecting snowball sampling data. Interviews and documentation use a tape recorder. A sample of 10 mothers married early, not continued to the husband and biological mother of the woman because the data was considered sufficient. Data analyzed by phenomenology are then presented in narrative / textual form. The results showed: almost all respondents were fulfilled (the right to live a reproductive life (pregnancy/ childbirth/ childbirth), a healthy, safe, free from sexual abuse / violence from the husband, the right of the mother to determine reproductive life (pregnancy/ childbirth/ childbirth) from discrimination, coercion / violence, respect for noble values, not degrading human dignity, in accordance with religious norms, the right to determine when (pregnant / giving birth), determine the number of children, distance of birth, family planning is medically healthy, does not conflict with religious norms ) Most of the respondents have the right to obtain information, education and counseling regarding reproductive health that is true and accountable.